Evaluation Of Ifraz Water Treatment Plants In Erbil City-Iraq - Siraj M. A. Goran (College of Education for Pure Sciences, 2010)
ABSTRACT With the increasing interest and care to Erbil province related with the priority for producing and supplying of potable water, three water treatment plants (WTP) were constructed during the last decades. Water quality for physical, chemical and bacteriological parameters were monitored in 15 sampling sites of three WTPs (Ifraz 1, 2 and 3) in Erbil governorate from May 2008 to Jan. 2009 at monthly interval period, each WTPs were divided in to five sampling sites according to treatment units. Results of water sample analysis were as follow: Turbidity values ranged between 0.2 to 29NTU, while pH values ranged from 7 to 8.3, and electrical conductivity were ranged from 340 to 773 µS.cm-1, total alkalinity and chloride ion were ranged from 92 to 181mg. CaCO3.l-1 and 8 to 28 mg.l-1 respectively. Total hardness for the studied sites were 128 to 308 mg.CaCO3.l-1, magnesium hardness is sure asses on calcium hardness. Dissolved oxygen (DO) values were ranged from 3.2 to 11.6 mg.l-¹. High BOD5 values were recorded in raw water and sedimentation units in all WTPs, while the low values were recorded in filtration and storage units of all WTPs at different times. Nitrite concentrations at the major treatment units estimated to be between (0.006 to 2.96 g at.N-NO2.l -1). Generally, potassium concentrations were lower than sodium. Sulphate concentration showed a range of 191 to 541 mg.l-1. The range of reactive phosphorus was between 0.15 to 10.5 µg.at.P-PO4.l-1, and Jar test results was between 4 and 28ppm. Bacteriologically, MPN for coliform.100ml-1 in treated waters were safe for drinking purposes according to WHO reports.